PERSEPSI DOSEN DAN MAHASISWA AKUNTANSI TERHADAP PROFESI AKUNTAN PUBLIK PASCA ENRONSTUDI KASUS PADA LIMA PTS DI JAKARTA BARAT - Henny Wirianata; Sofyan S. Harahap (Media Riset Akuntansi, Auditing & Informasi, 2007)
This study is a developed from DeZoort, et al (1997), Yeni (2001) and Abdullah and Selamat (2002), The objective is to know the perception of lecturers and students on public accountant profession post Enron scandal and to know whether there is a significant difference between them. Data is collected from questioners given to 5 private universities in West Jakarta with 210 respon-dents consist of 55 full-time lecturerrespondents and 155 accounting undergraduate students who have taken or is taking auditing subject. The study shows that not all lecturers and students know Enron Corporation scandal. In spite of that, lecturers and students who know and do not know, have positive perception in public accounting profession post Enron and there is no significant difference between them. While t-test result indicates that there is a significant difference percep-tion between lecturers' and accounting undergraduate students', especially in ethic and responsi-bility aspects, but not in knowledge and skill aspects. The result also shows lecturers have more positive perception than students do.Key words: Enron Corporation, academics, perception, public accountant profession, accounting lecturer, accounting student